1984
DOI: 10.1300/j251v03n04_02
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Drug Interactions with Alcohol

Abstract: Pharmacokinetic and pharmacodynamic factors play important roles in alcohol-drug interactions. The combined acute administration of alcohol and many other drugs may result in potentially harmful interactions especially when central nervous system depressants are involved. Often the mechanisms responsible for an adverse alcohol-drug interaction include inhibition of biotransformation and enhancement of the central depressant effects. Long-term ingestion of alcohol can lead to hepatic enzyme induction and in man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In our sample, one third of alcohol users and half of nicotine users had an additional SUD, compared to more than 80% of cannabis users and 90% of cocaine users. The accelerated speed of transition from cannabis or cocaine use to dependence given a previous history of a SUD may be mediated by conditioned learning processes, faster neuroadaptations (Leri et al, 2003; Schlaepfer et al, 2008) and drug interactions leading to slower biotransformation, decreases in adverse drug effects and overall enhanced drug effects (Bradberry et al, 1999; Kapusta et al, 2007; Leri et al, 2003; Mayer, 1984). Individuals dependent on more than one substance appear to have higher genetic liability and alleles of several genes have been associated with polysubstance abuse (Agrawal et al, 2008; Drgon et al, 2006; Schlaepfer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In our sample, one third of alcohol users and half of nicotine users had an additional SUD, compared to more than 80% of cannabis users and 90% of cocaine users. The accelerated speed of transition from cannabis or cocaine use to dependence given a previous history of a SUD may be mediated by conditioned learning processes, faster neuroadaptations (Leri et al, 2003; Schlaepfer et al, 2008) and drug interactions leading to slower biotransformation, decreases in adverse drug effects and overall enhanced drug effects (Bradberry et al, 1999; Kapusta et al, 2007; Leri et al, 2003; Mayer, 1984). Individuals dependent on more than one substance appear to have higher genetic liability and alleles of several genes have been associated with polysubstance abuse (Agrawal et al, 2008; Drgon et al, 2006; Schlaepfer et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…(184)(185)(186)(187)(188)(189) Amitriptyline Increase Amitriptyline was reported to decrease methadone clearance. It increases plasma AGP, thus increasing methadone binding.…”
Section: Metabolism and Excretionmentioning
confidence: 99%
“…In a study of five patients, no increase in methadone levels were observed 2 and 4 h after 90 mL of 50% ethanol solution taken 1 h after methadone administration 185 . However, the clinical perception is that alcohol-abusing, opioid-maintained patients have increased withdrawal between daily doses 184 , possibly due to increased drug metabolism by chronic ethanol consumption, whereas acute ethanol ingestion may inhibit microsomal drug metabolism 186 . Blood alcohol concentration (BAC) was reduced in methadone patients after administration of 14.7 g/70 kg of alcohol 1-2 h after methadone dosing (p < 0.05) 187 .…”
Section: Alcohol and Disulfirammentioning
confidence: 99%
“…http://thj.hums.ac.ir http concentration. Drug interactions can reduce the drug effectiveness, or even increase the plasma concentration and potential toxicity of a drug, leading to minor or serious unexpected side effects (6).…”
mentioning
confidence: 99%